PENGEMBANGAN MODEL PERKULIAHAN DARING DALAM MENINGKATKAN BERPIKIR HOTS MELALUI PEMAHAMAN ISI BACAAN MAHASISWA PRODI BAHASA INDONESIA IKIP SILIWANGI TAHUN 2020 - Rochmat Tri Sudrajat; Cecep Wahyu Hoerudin (STKIP Siliwangi, 2021)
A special model is needed to stimulate higher order thinking in students. Given a problem to be able to reach a high level of understanding, High Order Thinking Skill (HOTS) is also needed so that in the future students can be more productive and creative. This study aims as a development effort in improving reading skills through the HOTS mode. The research method used is quantitative or experimental research. The design used was a quasi-experimental research design. Then the subjects studied were the IKIP Siliwangi students for the academic year 2020-2021. The number of second-level students was 48 people. The score in the first cycle is 2.55 or has an achievement level of 51% which is in the qualification which is almost enough to be sufficient. The score in the second cycle is 3.41 or has an achievement level of 68.2% which is more than good enough qualification. Thus, there was a growth of 17.2% from cycle I. Meanwhile, the score for the third cycle or the last cycle was 3.80.